LDH as a prognostic marker in hypertensive pregnancy - Talwar, Prathap; Kondareddy, Triveni; C. A., Pranidha Shree (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Pregnancy induced hypertension (PIH) is a global problem with a 5-15% incidence rate in India and complicating 10-17% of all pregnancies. These are multisystem disorders and lead to a lot of cellular death. LDH is an intracellular enzyme and its level is increased in these women due to cellular death. So, serum LDH levels can be used to assess the extent of cellular death and thereby the severity of disease in this group of women. The objective of the study was to correlate the severity of the disease, maternal and perinatal outcome with Lactic Dehydrogenase (LDH) levels in serum in patients of preeclampsia and eclampsia. Methods: A prospective comparative study was conducted in the department of Obstetrics and Gynecology, JSS Medical Hospital, Mysore. Results: LDH levels were significantly elevated in women with preeclampsia and eclampsia (<0.001). Higher LDH levels had significant correlation with high blood pressure (P <0.10) as well as poor maternal and perinatal outcome. Conclusions: High serum LDH levels correlate well with the severity of the disease and poor outcomes in patients of preeclampsia and eclampsia.